Deadlier in the U.S.?: On lone wolves, terrorist groups, and attack lethality - Phillips, Brian J. (Terrorism and political violence, 2017)
Scholars, politicians, and pundits increasingly suggest lone wolf terrorists are substantial threats, but we know little about how dangerous these actors are—especially relative to other terrorist actors. How deadly are lone actor terrorists? A growing body of empirical research focuses on terrorist organizations, but similar work on lone actors is sparse. Furthermore, attempts to explicitly compare these or other types of terrorist actors are almost non-existent. This article considers theoretical arguments for why lone wolves ought to be especially lethal. However, it presents an argument for why terrorist groups should generally be more lethal. This argument is conditional upon the environment in which actors operate. Lone wolves should only be more deadly in states with especially strong counterterrorism capacity. The article uses data on terrorist attacks in fifteen developed countries, 1970–2010, to compare the lethality of terrorist acts. Around the world, attacks by organizations tend to be far more lethal than attacks by other actors. In the United States, however, lone wolves are generally the more lethal terrorist actors. This is argued to be because the robust counterterrorism capacity makes organized terrorism more difficult to accomplish.